PENGATURAN DAN PENERAPAN JAMINAN KEBEBASAN BERAGAMA SEBAGAI HAK ASASI MANUSIA DALAM PERSPEKTIF UUD 1945 SEBAGAI HUKUM DASAR NEGARA - Martin P Siringoringo (Nommensen Journal of Legal Opinion, 2022)
The guarantee of human rights through the 1945 Constitution of the Republic of Indonesia provides two meanings, first that the Indonesian Constitution contains the characteristics of a modern constitution, and secondly, it is the purpose of the state as a state of law (rechtstaat). This guarantee should be the basis for the protection of religious freedom which is one of human rights. However, the reality is that violations of religious freedom continue to increase, whether committed by individuals, groups, or the government. This thesis discusses Human Rights withthe understanding of Constitutionalism. The method used in this thesis is normative juridical. From the results of the analysis, one can conclude that even though freedom of religion is a human right that cannot be reduced under any circumstances. However, the Basic Law provides limitations in exercising religious freedom. In other words, that freedom of religion in Indonesia is not an absolute freedom. The guarantee of religious freedom is the responsibility of the state,especially the government as mandated by the 1945 Constitution of the Republic of Indonesia through legislation. The mandate is implemented in Indonesia in the Human Rights Law, the Law on Child Protection, the Law on the National Education System, the Law on Population Administration, and the Law on the Elimination of Racial and Ethnic Discrimination